Perubahan Status Gizi pada Anak Leukemia Limfoblastik Akut Selama Fase Kemoterapi - Alfi Karniawaty; Mirasari Putri; Lia Marlia Kurniawati (UNISBA Press, 2023)
Abstract: Chemotherapy contributes to malnutrition caused by side effects of chemotherapy drugs. This study aims to determine changes in nutritional status in patients with acute lymphoblastic leukemia (ALL). The research was conducted using the study literature method on searching data from Google Scholar using the keywords